Alpha-lipoic acid improves vascular endothelial function in patients with type 2 diabetes: a placebo-controlled randomized trial - Heinisch, B. B.; Francesconi, M.; Mittermayer, F.; Schaller, G.; Gouya, G.; Wolzt, M.; Pleiner, J. (European journal of clinical investigation, 2010)
Eur J Clin Invest 2010; 40 (2): 148–154 Objective  The aim of this study was to investigate the effect of alpha‐lipoic acid (ALA) treatment on endothelium‐dependent and ‐independent vasodilatation, assessed by forearm blood flow (FBF), in patients with type 2 diabetes mellitus. Research design and methods  A total of 30 subjects with type 2 diabetes were included in this randomized, controlled, double‐blinded, parallel group study. FBF responses to intra‐arterial acetylcholine (ACh) and glycerol trinitrate (GTN) were measured before and after 21 days of intravenous treatment with 600 mg alpha‐lipoic acid or placebo. Results  FBF responses were comparable at baseline. After treatment, FBF reactivity to ACh and GTN was unchanged in subjects receiving placebo. By contrast, ALA treatment increased endothelium‐dependent vasodilatation to ACh (P < 0·05) but not to GTN compared with baseline. Conclusions  Intravenous ALA treatment improves endothelium‐dependent vasodilatation in patients with type 2 diabetes, in the absence of effects on forearm vasomotor function. If this salutary action translates into vascular risk reduction remains to be established.